2020
DOI: 10.4103/ija.ija_528_20
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of laparoscopy-guided with ultrasound-guided subcostal transversus abdominis plane block in laparoscopic cholecystectomy – A prospective, randomised study

Abstract: Background and Aims: Subcostal transversus abdominis plane (TAP) block is usually done under ultrasound guidance in laparoscopic cholecystectomy. Laparoscopic-guided subcostal TAP block is an alternate technique where ultrasound is not available. Our primary objective was to compare the success rate of ultrasound and laparoscopic approaches to the subcostal TAP block. The secondary objectives were to assess the duration of postoperative analgesia and morphine consumption postoperatively for 24 h. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…All included studies were of moderate or high quality based on JADAD Score ( Table 2 ). Out of 23 included studies, 14 studies ( 16 18 , 23 25 , 27 , 30 , 31 , 34 38 , 40 ) were conducted in Caucasian individuals, with the remaining nine studies ( 19 22 , 26 , 28 , 29 , 32 , 33 ) were conducted on an Asian population.…”
Section: Resultsmentioning
confidence: 99%
“…All included studies were of moderate or high quality based on JADAD Score ( Table 2 ). Out of 23 included studies, 14 studies ( 16 18 , 23 25 , 27 , 30 , 31 , 34 38 , 40 ) were conducted in Caucasian individuals, with the remaining nine studies ( 19 22 , 26 , 28 , 29 , 32 , 33 ) were conducted on an Asian population.…”
Section: Resultsmentioning
confidence: 99%
“…The morphine consumption following subcostal TAP block in laparoscopic cholecystectomy was 4.72 ± 0.94 mg in another study, well matching our results. 9 Eldawlatly et al observed lesser morphine consumption in laparoscopic cholecystectomy patients who received subcostal TAP block than the control group (22.8 mg vs 10.5 mg). 10 Shin et al demonstrated lesser fentanyl consumption in patients receiving subcostal TAP in laparoscopic cholecystectomies.…”
Section: Discussionmentioning
confidence: 96%
“…The TAP block was commonly used for post-operative analgesia that lowers opioid consumption for patients with obesity [35]. The TAP technique has evolved and can be guided by either ultrasound or LAP guidance [38].…”
Section: Discussionmentioning
confidence: 99%